When failure is not an option: a police firearms training concept for improving decision-making in shoot/don’t shoot scenarios - Olma, Joshua; Sutter, Christine; Sülzenbrück, Sandra (Frontiers in Psychology, 2024)
Sometimes, policing requires a quick and correct assessment of potentially hazardous situations. The training of tactical gaze control and visual attention, and its positive impact on efficient shoot/don't shoot decisions in police cadets' use of firearms has recently been demonstrated in a field study (Heusler & Sutter, 2022). Inspired by the latter, we designed an individual video-based police firearms training that was grounded on the Four-Component Instructional Design Model (4C/ID; van Merrienboer, 2020). We shifted towards an individual blended learning approach where we applied an intervention training focussed on situational awareness, tactical gaze control, and visual attention. In a preregistered lab experiment, N = 45 senior police officers were randomly allocated to the intervention training or an active control training that resembled a traditional police firearms training. Both groups watched a self-produced educational video before proceeding to the practical training in our indoor firing range. In a pre-and post-test, they engaged in realistic shoot/don't shoot video scenarios. Both groups did very well regarding decision-making, the optimal muzzle position, and the tactical conduct to keep both eyes open before shooting. Although both groups performed on a comparable level in the pre-test's shoot scenarios, the intervention group significantly improved their response times and time until the first hit. Overall, we were able to provide an adapted, didactically based police firearms training that supplements current standards. We demonstrated that experts are still susceptible to innovative training concepts and therefore substantiate the recommendation to devote more attention to approaches that emphasize the importance of situational awareness, tactical gaze control, and visual attention in police firearms training.